The global textile and apparel value chain: From Mexico-US-China linkages to a global approach - Óscar Rodil-Marzábal; Ana Laura Gómez Pérez; Hugo Campos-Romero (Economies, 2022)
The aim of this paper is to analyze the participation in the global textile and apparel value chain with special attention, first, to the case of three dynamic and interrelated economies (Mexico, the United States, and China); and second, to a general approach to a larger sample of countries through the analysis of trade in value added. From the descriptive analysis, a high domestic share in each country's exports is found. However, China is the leading exporter in the industry, accounting for around a third of the domestic value added in the global textile final demand. An econometric estimation has also been carried out to observe the effects of tariffs, FDI, and labor costs on the total and backward participation in the textile GVC. In this case, the sample has been extended to 39 developed and 22 developing countries. The results reveal tariff protection as a determinant of the degree of participation of the sector, especially when backward participation and developing economies are considered. However, FDI and labor costs only show the expected results in the case of developing countries. This may be due to the different tasks performed by developing economies (primarily manufacturing) versus developed economies (branding, design) within the sector's value chain.
Keywords: 330; developed and developing countries; explanatory factors; forward and backward participation; global value chain; international trade; textile and apparel